Study on Vibration Damping Characteristics of Mounting Structure Based on the High Damping Alloy Material - Junzhe Lin; Wenbiao Li; Haiyang Chen; Hongxu Zhang; Yulai Zhao; Hui Ma; Qingkai Han (Applied Sciences)
The high damping alloy materials, by virtue of the excellent mechanical properties and damping performance generated by the material’s properties and internal friction mechanism, can be employed directly in the reduction of structural vibrations. On the basis of summarising the current research progress and application status of existing damping alloy materials, the damping characteristics of Fe-12Cr-3Al ferromagnetic high damping alloy material were tested and applied to the vibration reduction of an aero-engine lubricating oil tank. Subsequent to this, vibration characteristics simulation analysis and tests were conducted. The results show that the amplitude reduction rate of mounting structures utilising the Fe-12Cr-3Al ferromagnetic high damping alloy is 30% in comparison to Q235 carbon steel. Additionally, the vibration transmission rate can be diminished by 40%. The utilisation of the Fe-12Cr-3Al ferromagnetic high damping alloy in the aero-engine mounting structure has been observed to result in a discernible reduction in vibration.